Correlation Between Rheumatoid Arthritis Activity with Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio: A Case-Control Study - Hussein, Safinaz; M Tawfik, Nabawia; Abdelrahman, Noha F; Abobakr, Asmaa; Hafez, Rania; Thabet, Marwa M (Clinical Medicine And Health Research Journal, 2023)
Background: Patients with Rheumatoid arthritis (RA) may suffer from joint deformity, due to the inflammatory process in active disease. Inflammation may lead to disability in patients with RA. The neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) have been emerged as markers of many inflammatory diseases including RA. The aim of this study was to evaluate the role of NLR and PLR ratios in the evaluation of RA activity and their relation with DAS-28 that is already used for the assessment of RA disease activity. Our patients were divided into group A (patients with active disease, DAS-28 > 2.6) and group B (patients with remission, DAS-28 < 2.6). The patients with active disease were subdivided into three subgroups (patients with high disease activity with DAS-28 > 5.1, moderate disease activity patients with DAS-28 > 3.2, and low disease activity patients with DAS-28 <3.2 and >2.6). Results: NLR and PLR are significantly higher in patients with RA than in healthy people and higher in patients with active disease than those in remission and significantly positively correlated with RA activity. Conclusion: Both NLR and PLR are two inflammatory markers that are useful in evaluating RA disease activity as they are simple, cheap, and objective markers.